Disability accommodation experiences of social work students in the United States. Issue 7 (3rd October 2021) - Sellmaier, Claudia; Kim, Jaeran
ABSTRACT: Social work students with disabilities navigate accommodations as part of their post-secondary education, but there is still limited research about how they use and access program and campus supports. This study explored the accommodation experiences of 262 U.S. students who identified as having a disability. Participants were enrolled in BASW (52.1%), MSW (44.4%) and PhD/DSW (3.4%) programs. Quantitative analysis found that 56.4% were registered with disability resources, 47.1% received classroom, and 14.8% field accommodations. Type of disability was only a significant predictor of receiving field accommodations. Employment status was a significant predictor of both registering with disability resources, and receiving classroom accommodations. Open-ended survey responses from disabled students illustrated the varied supports and challenges students navigated on campus and within the classroom and field while enrolled in their social work programs. We discussed how these findings provide social work programs opportunities to consider ways to increase practices that support students with disabilities.